Computational fluid dynamics approach for performance evaluation of a solid oxide electrolysis cell for hydrogen production. (1st January 2015) - Navasa, Maria; Yuan, Jinliang; Sundén, Bengt
Highlights: A three-dimensional FVM based CFD model for a cathode-supported SOEC is developed. The effect of different operating voltages on cell performance is investigated and analyzed. Cross-flow and parallel-flow configurations are compared and differences are identified. Abstract: A finite volume method based computational fluid dynamics model has been developed and applied for a cathode-supported planar solid oxide electrolysis cell (SOEC) operating in cross-flow configuration arrangement. The performance behavior, in terms of current density, temperature distribution and hydrogen production in an SOEC, has been investigated for different operating voltages and compared with a corresponding parallel-flow configuration. The predicted results show that higher current densities are obtained for higher operating voltages. The anodic current density is higher than the cathodic one. Yet, the parallel-flow configuration yields lower current density values although they remain in the same order of magnitude as those from the cross-flow arrangement. The simulation reveals various temperature profiles depending on the operating voltage emphasizing the three thermal operating modes of an SOEC, i.e., endothermic, thermo-neutral and exothermic. Per contra, the parallel-flow arrangement gives a temperature decrease along the flow direction although operating in exothermic mode. Higher hydrogen molar fractions at the outlet of the cathode channel were obtained at higher operating voltages due to the higher current densities generated and the exothermic operating mode. The parallel-flow arrangement yields lower hydrogen production due to the lower current densities revealed.